Cinder creative coding cookbook : create compelling animations and graphics with Kinect and camera input, using one of the most powerful C++ frameworks available /: create compelling animations and graphics with Kinect and camera input, using one of the most powerful C++ frameworks available. (2013) - Unknown
No abstract available